OXA1L deficiency causes mitochondrial myopathy via reactive oxygen species regulated nuclear factor kappa B signalling pathway - Yongkun Zhan; Qian Wang; Ya Wang; Yanjie Fan; Dan Yan; Xianlong Lin; Yaoting Chen; Tingting Hu; Nan Li; Weiqian Dai; Hezhi Fang; Yongguo Yu (Clinical and Translational Medicine, 2025)
Abstract Background OXA1L is crucial for mitochondrial protein insertion and assembly into the inner mitochondrial membrane, and its variants have been recently linked to mitochondrial encephalopathy. However, the definitive pathogenic link between OXA1L variants and mitochondrial diseases as well as the underlying pathogenesis remains elusive. Methods In this study, we identified bi‐allelic variants of c.620G>T, p.(Cys207Phe) and c.1163_1164del, p.(Val388Alafs*15) in OXA1L gene in a mitochondrial myopathy patient using whole exome sequencing. To unravel the genotype–phenotype relationship and underlying pathogenic mechanism between OXA1L variants and mitochondrial diseases, patient‐specific human‐induced pluripotent stem cells (hiPSC) were reprogrammed and differentiated into myotubes, while OXA1L knockout human immortalised skeletal muscle cells (IHSMC) and a conditional skeletal muscle knockout mouse model was generated using clustered regularly interspaced short palindromic repeats/Cas9 genomic editing technology. Results Both patient‐specific hiPSC differentiated myotubes and OXA1L knockout IHSMC showed combined mitochondrial respiratory chain defects and oxidative phosphorylation (OXPHOS) impairments. Notably, in OXA1L‐knockout IHSMC, transfection of wild‐type human OXA1L but not truncated mutant form rescued the respiratory chain defects. Moreover, skeletal muscle conditional Oxa1l knockout mice exhibited OXPHOS deficiencies and skeletal muscle morphofunctional abnormalities, recapitulating the phenotypes of mitochondrial myopathy. Further functional investigations revealed that impaired OXPHOS resulting of OXA1L deficiency led to elevated reactive oxygen species production, which possibly activated the nuclear factor kappa B signalling pathway, triggering cell apoptosis. Conclusions Together, our findings reinforce the genotype–phenotype association between OXA1L variations and mitochondrial diseases and further delineate the potential molecular mechanisms of how OXA1L deficiency causes skeletal muscle deficits in mitochondrial myopathy. Keypoints OXA1L gene bi‐allelic variants cause mitochondrial myopathy. OXA1L deficiency results in combined mitochondrial respiratory chain defects and OXPHOS impairments. OXA1L deficiency leads to elevated ROS production, which may activate the NF‐κB signalling pathway, disturbing myogenic gene expression and triggering cell apoptosis.